The effect of oxygen mobility/vacancy on carbon gasification in nano catalytic dry reforming of methane: A review - Siti Nor Amira, Rosli; Sumaiya, Zainal Abidin; Osazuwa, Osarieme Uyi; Fan, Xiaolei; Jiao, Yilai (Elsevier, 2022)
Dry reforming of methane (DRM) remains challenging due to catalyst deactivation driven primarily by carbon deposition and metal sintering. Nanocatalytic materials offer great activity and stability in the DRM reaction due to the high dispersion of ultrasmall metal nanoparticles. Here we present a designated review on the role of the catalyst’s oxygen mobility/vacancy in carbon gasification during the DRM reaction. The presence of mobile oxygen and/or oxygen vacancy in nanocatalysts is significantly beneficial to react with the deposited carbon in-situ during the DRM reaction. This review first discusses the state-of-the-art nanocatalysts being applied in the DRM reaction. Then, the effects of the type and physicochemical properties of the nanocatalysts on their catalytic performance in the DRM are outlined, followed by the elaboration of carbon gasification route/mechanism in the DRM reaction. Finally, a critical discussion on the kinetics of carbon gasification is detailed. This review can serve as a current knowledge base to encourage the continuous development of in-depth study of this promising catalytic field, especially the development of active yet stable nanocatalysts, which can contribute to valorization of carbon emissions.